2012
DOI: 10.5430/jnep.v2n3p162
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based nursing education: An integrative review of empirical studies

Abstract: The goal of this study is to explore the ways in which Computer-Based Nursing Learning (CBNL) has been studied and the findings that have been made with regard to its use in undergraduate nursing education. We undertook an integrative review by selecting papers published in English between 2007 and 2010. We included in the review empirical studies comparing CBNL with other training strategies for clinical skills education in the context of undergraduate nursing education. We carried out an electronic search in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Entretanto, é recomendada a participação de três a dez juízes na validação de conteúdo, tendo em vista a experiência acumulada e pelo fato de o julgamento ser feito individualmente 22 . A evidência de validade do conteúdo de instrumento usado em pesquisa, por dois ou mais avaliadores, exclui a subjetividade e atribui confiabilidade aos resultados 23 .…”
Section: Discussionunclassified
“…Entretanto, é recomendada a participação de três a dez juízes na validação de conteúdo, tendo em vista a experiência acumulada e pelo fato de o julgamento ser feito individualmente 22 . A evidência de validade do conteúdo de instrumento usado em pesquisa, por dois ou mais avaliadores, exclui a subjetividade e atribui confiabilidade aos resultados 23 .…”
Section: Discussionunclassified
“…CAI methods can achieve excellent results, with students' reading and speaking abilities being continuously enhanced during the learning process. 11 There is limited empirical evidence regarding the effectiveness of CAI in clinical skills education. 12 A previous study in Information and Communication Technologies (ICTs) found many obstacles to CAI nursing education.…”
Section: Discussionmentioning
confidence: 99%
“…12 A previous study in Information and Communication Technologies (ICTs) found many obstacles to CAI nursing education. 11 They reported age, previous knowledge, and preferred learning style as factors that affected learning of nursing clinical skills. They also recommended the following research guidelines for studies investigating CAI instruction: randomized controlled trial study design, avoid voluntary recruitment, and test for differences in the demographic characteristics of participants in the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…combining quantitative and qualitative data) to investigate the state of the art of computer-aided nursing education pedagogies before and after the COVID-19 era. Other SLRs were conducted in a similar research domain, such as [13], which examined computer-based nursing education only in undergraduate nursing students. However, this study might not reflect recent developments, as it was conducted between 2007 and 2010, including 9 studies only.…”
Section: Contributionsmentioning
confidence: 99%